The Mens Rea of Human Trafficking: The Case of Migrant Domestic Workers - Demetriou, Daphne (International criminal justice review, 2019)
Efforts to eradicate human trafficking continue, with the 2017 Trafficking in Persons Report calling on governments to improve the detection and prosecution of all involved in this crime, with specific reference to recruitment agencies. Yet despite calls to examine the wider scope of potential trafficking perpetrators, an important element remains problematic; namely, establishing that all involved in the recruitment and movement of individuals possess the requisite mental element for this crime. This article examines this mental element and applies it to the different actors commonly involved in the migration and alleged trafficking of migrant domestic workers. The article concludes that establishing such experiences as human trafficking and attributing the mental element of the offense to all people in the supply chain becomes less attainable. The flexibility permitted under the United Nations Trafficking Protocol, as to the national threshold for the crime’s mens rea, has resulted in disparities as to what and who the crime of human trafficking encompasses. The specific intent element of the Protocol is at odds with the constructive knowledge element incorporated in some states, a reality that runs counter to the intentions of the Protocol’s drafters for a unified definition and jeopardizes the prosecution of trafficking cases. In rectifying this, it is pivotal for states to ensure that alternative legal provisions are available to capture those who often pave the way to migrant domestic workers’ exploitation.